Uma interpretação à luz da ideologia de discursos sobre o bebê e a creche captados em cursos de pedagogia da cidade de São Paulo - Secanechia, Lourdes Pereira de Queiroz (2011)
This research is part of the collective effort of the NEGRI - Center of Studies of Gender, Race and Age of the Postgraduate Studies Program in Social Psychology at the Pontifícia Universidade Católica de São Paulo (PUC-SP) - to understand the process of social construction of childhood in Brazil. For this purpose, we have analyzed discourses of social actors who occupy privileged positions in the arena of political negotiations for the young child. In this dissertation, we aim to provoke, describe and interpret speeches captured through the transcription of interviews, teaching plans of the disciplines of the Education Course about the baby, their care and education in day care centers. The Higher Education Institutions to which these teachers are linked offer a large number of vacancies authorized by the MEC for the Faculty of Education in the city of São Paulo. The initial hypothesis of this research was centered on the assumption that teachers of higher education as producers and receivers of symbolic forms could establish, or not, babies and day care centers in a position of inferiority in relation to other ages and other stages of education. The theoretical framework was constituted in light of the theory of ideology (THOMPSON, 2009) and Social Studies of Childhood. The depth hermeneutics (THOMPSON, 2009) and the techniques of content analysis (BARDIN, 1977 and ROSEMBERG, 1981) were used as theoretical basis for the analysis of the curriculum of the disciplines and the transcripts of the interviews. The invisibility of the small child caught in the teaching plans of the disciplines and the voices of the teachers of the Education course can be interpreted as a strategy of operation of ideology. On this account, promoting the initial training of teachers who will be able to educate and care for young children in day care centers, the IES demonstrated dissimulation in addition to hiding relations of age domination in the brazilian educational scenario